The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1038/s41390-018-0063-3
|View full text |Cite
|
Sign up to set email alerts
|

Defining outcomes following congenital diaphragmatic hernia using standardised clinical assessment and management plan (SCAMP) methodology within the CDH EURO consortium

Abstract: Treatment modalities for neonates born with congenital diaphragmatic hernia (CDH) have greatly improved in recent times with a concomitant increase in survival. In 2008, CDH EURO consortium, a collaboration of a large volume of CDH centers in Western Europe, was established with a goal to standardize management and facilitate multicenter research. However, limited knowledge on long-term outcomes restricts the identification of optimal care pathways for CDH survivors in adolescence and adulthood. This review ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 115 publications
0
29
0
2
Order By: Relevance
“…The cardiopulmonary incremental exercise test appears as an efficient tool to assess respiratory morbidity associated with QOL impairment. Finally, the development of disease‐specific QoL questionnaires could improve the assessment of QOL in children with CDH repair 29 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cardiopulmonary incremental exercise test appears as an efficient tool to assess respiratory morbidity associated with QOL impairment. Finally, the development of disease‐specific QoL questionnaires could improve the assessment of QOL in children with CDH repair 29 …”
Section: Resultsmentioning
confidence: 99%
“…Finally, the development of disease-specific QoL questionnaires could improve the assessment of QOL in children with CDH repair . 29…”
Section: Con Clus Ionmentioning
confidence: 99%
“…This is why a close long-term follow-up in a multidisciplinary clinic is required, though sufficient data on the ideal length and frequency of visits of follow-up has not been found yet. This is due to the fact that most studies are single center studies and include small numbers of patients 56 . In this review the focus was mainly on short term complications in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Rameshwar Prasad Department of Neonatology, Rajendra Institute of Medical Sciences, Ranchi, Jharkhand, India *Address all correspondence to: drrameshwarprasad@hotmail.com hypertension, obstructive pulmonary disease, reduced exercise capacity, recurrent pulmonary infection), gastroesophageal reflux, nutritional derangements, neurodevelopmental delays, hernia recurrence, hearing deficits and orthopedic deformities [179,180]. The Health-related Quality of Life (HRQoL) has been reported to improve as the survivors grow older, while it may be variably compromised during the childhood [181][182][183][184].…”
Section: Author Detailsmentioning
confidence: 99%
“…The guidelines for the follow-up of CDH survivors have been outlined by the American Academy of Pediatrics and are available [179]. A review of current follow up practices in CDH EURO consortium centers revealed that even though 15 out of 19 centers had structured and standardized follow up program for the CDH patients, the annual follow up until 16 years of age was not done in any of the participating centers [180]. The study group proposed the implementation of standardized follow-up of CDH patients for extended evaluation of the survivors for their long term outcomes [180].…”
Section: Author Detailsmentioning
confidence: 99%